THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND WORK CULTURE TO LECTURES’ PERFORMANCE - Bakti, Erwin (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
The objective of this study was to find out the influence of transformational leadership and work culture on lecturer’s performance of Universitas Muhammadiyah Palembang. This study used quantitative approach, survey method and path analysis. The data was taken from 204 lecturers and 29 heads of study program became the sample in this study. The result of the study found that (1) transformational leadership gave direct positive influence on the performance; (2) work culture gave direct positive influnce on lecturer’s performance; and (3) transformational leadership gave direct positive influnce on work culture. Form the research has been conducted, it could be concluded there must be the improvement of transformational leadership and work culture to improve the lecturer’s performance of Universitas Muhammadiyah Palembang. Keywords:Transformational Leadership, Work Culture, lecture’s Performance.